Cardiovascular involvement in Epstein–Barr virus infection - Chen, Xinying; Li, Yingying; Deng, Lijun; Wang, Lianyu; Zhong, Wenting; Hong, Junbin; Chen, Liyu; Yang, Jinghua; Huang, Bin; Xiao, Xiaolan (Frontiers in Immunology, 2023)
Cardiovascular involvement is an uncommon but severe complication of Epstein-Barr virus infection, caused by direct damage and immune injury. Recently, it has drawn increasing attention due to its dismal prognosis. It can manifest in various ways, including coronary artery dilation (CAD), coronary artery aneurysm (CAA), myocarditis, arrhythmias, heart failure, etc. If not treated promptly, cardiovascular damage can progress over time and even lead to death, which poses a challenge to clinicians. Early diagnosis and treatment can improve the prognosis and reduce mortality. However, there is a lack of reliable large-scale data and evidence-based guidance for managing cardiovascular damage. Consequently, in this review, we attempt to synthesize the present knowledge of cardiovascular damage associated with EBV and provide an overview of the pathogenesis, classification, treatment, and prognosis, which may enhance the recognition of cardiovascular complications related to EBV and is valuable to clinical management.